PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN METODE PEMECAHAN MASALAH (PROBLEM SOLVING) UNTUK PENINGKATAN PRESTASI BELAJAR GEOGRAFI SISWA KELAS X IPS SEMESTER GENAP SMA NEGERI 7 DENPASAR TAHUN PELAJARAN 2018-2019 - Sudarsana, Putu Agus (Widyadari: Jurnal Pendidikan, 2019)
The purpose of this study was to find out how high an increase in student learning achievement after applied Problem Based Learning learning models in geography learning. This research was carried out in the 7th Public High School in Denpasar in Class X IPS with the ability of students to study lithosphere dynamics and their impact on life is quite low. The data collection method is a learning achievement test. The data analysis method is descriptive both for qualitative data and for quantitative data.       The results obtained from this study are Problem Based Learning can improve student learning achievement. This is evident from the results obtained initially reaching an average value of 69.58 in the first cycle reaching an average value of 75.86 in the second cycle. The Problem Based Learning model can provide answers according to the purpose of this study. So the Problem Based Learning model is very effective applied in the learning process which results in active, enthusiastic and able students to understand the material being taught so that student learning achievement becomes increased